PENGARUH PERAN INTERNAL AUDIT, MORALITAS DAN KESESUAIAN KOMPENSASI TERHADAP PENCEGAHAN KECURANGAN AKUNTANSI - Ida Bagus Gaga Surya Prabawa; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2021)
Fraud in the financial statements is committed due to misstatement or intentional or unintentional impact both material and non-material. These mistakes must be avoided because they will have a detrimental impact on the company and outsiders such as the editorial party, the government and shareholders. Fraud prevention is an activity that is carried out in terms of establishing policies, systems and procedures that help ensure that the necessary actions have been taken by the board of commissioners, management and other personnel in the company to be able to provide adequate assurance in achieving organizational goals. This study aims to determine the effect of the role of internal audit, morality and the suitability of compensation on the prevention of accounting fraud. This research was conducted at PT. Puri Santrian. The sample in this study were 40 employees. The data were tested using the classical assumption test, multiple linear regression analysis, hypothesis testing and the coefficient of determination. The results showed that the internal audit role variable had a positive and significant effect on the prevention of accounting fraud. Morality has a positive and significant effect on the prevention of accounting fraud. Compensation suitability has a positive and significant effect on the prevention of accounting fraud.